LIGHTING IN PRODUCTION AND ITS STANDARDS. NATURAL AND ARTIFICIAL LIGHTING - Yulchiyev Mash'albek Erkinovich,; Yusupov Asadbek G`ulom o`g`li, (Лучшие интеллектуальные исследования, 2024)
Annotation: The article discusses the importance of lighting in buildings, its impact on human health, lighting standards and requirements, as well as methods of lighting buildings: natural, artificial and mixed lighting. At the same time, when and where to use these types of lighting, their advantages and disadvantages will be discussed.